OLDER ADULTS' EVERYDAY MEMORY BELIEFS AND ATTRIBUTIONS: A QUALITATIVE INTERVIEW ANALYSIS. (11th November 2018) - Lustig, E; Hertzog, C; Pearman, A; Waris, A
Abstract: How older adults describe the causal factors involved in memory successes and failures interplays with their beliefs about their own memory abilities and the behaviors they engage in to support their everyday remembering. Questions remain about how their beliefs and attributions about memory promote or deter the use of everyday memory strategies. This study evaluated these issues through qualitative coding of 26 individually tailored, semi-structured interviews with older adults ages 62–83 (M=69.5, SD=5.72) concerning their everyday remembering. The interviews were focused on how older adults implemented memory strategies, how efficacious these procedures were in helping them achieve their goals, and how they conceptualized their behaviors. The interviews provided a greater understanding of the context and depth in which memory failures occurred. We focus on one of the major emergent themes, beliefs and attributions about memory. Habits and partially-structured routines were not typically directly attributed as the causes of successful daily remembering. However, these behaviors were mentioned when people were asked about how they accomplished tasks and goals. Participants also reported that important things would be remembered, regardless of strategy use or memory-supportive behaviors, and stated that forgetting was usually about inconsequential things. This "importance" belief was observed in tandem with reports of forgetting significant events (e.g. a spouse's birthday). Finally, when everyday memory issues were acknowledged, they were often attributed to age-related declines in memory and viewed as being inherently uncontrollable.